Taishan Pinus massoniana Pollen Polysaccharides Enhance Immune Responses in Chickens Infected by Avian Leukosis Virus Subgroup B. (4th July 2018) - Yang, Shifa; Li, Guiming; Zhao, Zengcheng; Huang, Zhongli; Fu, Jian; Song, Minxun; Lin, Shuqian; Zhu, Ruiliang
ABSTRACT: Immunosuppressive virus, which can cause suppressed immunity and vaccination failure, frequently occurs in chicken flocks and seriously destroys the poultry industry. Our previous studies have reported that Taishan Pinus massoniana pollen polysaccharide (TPPPS) possess immunomodulatory effects and improve the immune effects of vaccines. In this study, avian leukosis virus subgroup B (ALV-B) was chosen as immunosuppressive virus to artificially establish immunosuppressive models in chickens, and the immune modulatory ability of TPPPS on the immune response of chickens was evaluated. Four randomly assigned groups (Group I–IV) of these immunosuppressed chickens were administered with TPPPS at doses of 0, 100, 200, and 400 mg/kg (every kilogram chick), respectively. Group V was administered with saline as control. At seven day old, 10 chickens randomly selected from Group I–V were inoculated with the attenuated Newcastle disease (ND) vaccine. The results showed that during the monitoring period, TPPPS significantly enhanced weight of immune organs, peripheral lymphocyte proliferation, the percentage of CD4+ and the ratio of CD4+/CD8+, IL-2 and IFN-γ production, and ALV-B antibody positive rate of chickens in a dose-dependent manner, with 400 mg/kg TPPPS being the most effective. In addition, the antibody titer against Newcastle disease virus (NDV) in Group IV with 400 mg/kg was significantly higher than those in other groups. We observed the stronger immunity in the TPPPS group, which indicates that TPPPS could be used as an immunoenhancer to relieve immunosuppression caused by ALV-B in the poultry industry.